P272 Improvements in exacerbation rates with single inhaler triple therapy versus dual ics/laba therapy in patients with advanced chronic obstructive pulmonary disease (copd): subgroup analyses of the phase iii fulfil study. (15th November 2017) - Hilton, E; Brealey, N; Birk, R; Zhu, C-Q; Criner, GJ; Dransfield, MT; Halpin, D; Lomas, DA; Lipson, DA
Abstract : Results from FULFIL have shown statistically significant improvements in lung function and health-related quality of life, and a reduction in exacerbation rates with once-daily fluticasone furoate/umeclidinium/vilanterol (FF/UMEC/VI) 100 µg/62.5 µg/25 µg administered using a single ELLIPTA ® inhaler compared with twice-daily budesonide/formoterol (BUD/FOR) 400 µg/12 µg using the Turbuhaler ® in patients with symptomatic COPD at risk of exacerbations. The safety profile of FF/UMEC/VI reflected that of the components (Lipson, et al. Am J Respir Crit Care Med. 2017). Herein we present post-hoc subgroup analyses of exacerbation rates by prior COPD medication class, disease severity and exacerbation history during FULFIL. In the intent-to-treat (ITT; 24 weeks) population, the mean annual exacerbation rate, FF/UMEC/VI versus BUD/FOR ratios and annual exacerbation rates reductions were calculated for subgroups: by prior COPD medication class, inhaled corticosteroid (ICS) +long acting beta agonists (LABA); BUD/FOR; ICS +LABA + long-acting muscarinic antagonists (LAMA); LAMA; tiotropium; LAMA +LABA; by disease severity, forced expiratory volume in 1 s (FEV1 ) <50% predicted, no moderate/severe exacerbation; FEV1 <50%, ≥1 moderate/severe exacerbation; FEV1 ≥50–≤80%, ≥2 moderate or ≥1 severe exacerbations; and by exacerbation history, 0/1 moderate exacerbations;≥2 moderate exacerbations;≥1 severe exacerbation. Up to Week 24 in the ITT population, FF/UMEC/VI versus BUD/FOR improved the mean annual exacerbation rate (range, 63%–24%) in all prior medication subgroups, except LAMA +LABA (annual exacerbation rate reduction, −44%) and improved mean annual exacerbation rates in all disease severity (range, 45%–27%) and exacerbation prior history (range, 57%–27%) subgroups (Table). Statistical significance of the FF/UMEC/VI:BUD/FOR ratio was observed for the subgroups: prior medication class ICS +LABA (0.37; 95% confidence interval [CI] 0.20–0.71; p=0.003) and ICS +LAMA + LABA (0.53; 95% CI 0.33–0.87; p=0.012); disease severity FEV1 <50% and≥1 moderate/severe exacerbation (0.55; 0.34–0.89; p=0.015); exacerbation history 0/1 prior moderate exacerbation (0.62; 0.44 0.87; p=0.005) and ≥1 prior severe exacerbation (0.43; 0.22 0.86; p=0.017) (Table). Improvements in mean annual exacerbation rates with once-daily FF/UMEC/VI compared with twice-daily BUD/FOR were observed in all patients regardless of disease severity or exacerbation history and all prior COPD medication class subgroups except for LAMA +LABA. Funding: GSK (NCT02345161 ; CTT116853) Please refer to page A260 for declarations of interest in relation to abstract P272.